Molecular Imaging Aided Improvement in Drug Discovery and Development - Chaudhury, Smrita; Thakur, Bhushan; Chatterjee, Subhoshree; Ray, Pritha (Current Biotechnology, 2014)
The current drug discovery and development platform is rapidly expanding with new classes of pharmaceuticals and novel biological information. The drug discovery and development process relies on the utilization of relevant and robust tools, methods, and models that are predictive of clinical effects in terms of diagnosis, prevention, therapy and prognosis. One of the methods that have gained prominence over the years is Molecular Functional Imaging that optimizes and ensures delivery, measures efficacy and toxicity of the therapeutic agents to the target cell or site in pre-clinical setting. Currently three different imaging modalities that include Radionuclide Imaging (Positron Emission Tomography or PET and Single Photon Emitted Computed Tomography or SPECT), Magnetic Resonance Imaging (MRI) and Optical Imaging (Bioluminescence and Florescence) are being extensively used in preclinical models to assess the pharmacokinetics, functional alteration of target and other sites and efficacy of treatment. These real time monitoring modalities are promoting development of novel and sophisticated molecular technologies to identify modulators of protein-protein interactions, apoptosis, protease actions and various other physiological responses. In parallel, significant paradigm shift is occurring at drug discovery and development landscape through emergence of several drug delivery systems like hydrogels, polymers, liposomes and nanoparticles. These innovative delivery vehicles are the future of modern personalized medicine which is still in experimental phases. Molecular Imaging techniques are again the final validation tools for determining the safety, efficacy and need of further improvement of these delivery vehicles. In this review we discuss the current and evolving state of drug discovery and development aided by functional molecular imaging techniques.
Keywords: high throughput screening